Optimizing thermal efficiencies of power-law fluids in double-pass concentric circular heat exchangers with sinusoidal wall fluxes - Ho, C.-D. (American Institute of Mathematical Sciences, 2022)
Effect of external-recycle operations on the heat-transfer efficiency, specifically for the power-law fluid flowing in double-pass concentric circular heat exchanger under sinusoidal wall fluxes, is investigated theoretically in the developed countries. Given that the fluid is heated twice on both sides of the impermeable sheet, four flow patterns proposed in recycling double-pass operations are expected to make substantial improvements in the performance of heat exchanger device in this study. Theoretical predictions point out that the heat-transfer efficiency increases with the ratio of channel thickness of double-pass concentric circular heat exchanger for all new designs under the same working dimension and the operational condition. The fluid velocity within the double-pass heat exchanger is increased by the fluids flowing through divided subchannels, which contributed to the higher convective heat-transfer efficiency. A simplified mathematical formulation was derived for double-pass concentric circular heat exchangers and would be a significant contribution to analyze heat transfer problems with sinusoidal wall fluxes at boundaries. The results deliver the optimal performance for the proposed four configurations with the use of external recycle compared to those conducted in single-pass, where an impermeable sheet is not inserted. The influences of power-law index and impermeable-sheet position on average Nusselt numbers under various flow patterns are also delineated. The distribution of dimensionless wall temperature was lower at the level of relative smaller thickness of annular channel, and the average Nusselt numbers for four external-recycle configurations and single-pass device were more suitable for operating under same condition. The ratio of the power consumption increment to heat-transfer efficiency enhancement demonstrates the economic feasibility among various configurations of double-pass concentric circular heat exchanger. The results also show that the external-recycle configuration (say Type B in the present study) serves as an important economic advantage in designing concentric circular heat exchangers for heating power-law fluids due to the smaller volumetric flow rate in annular channel with exiting outlet temperature. Â©2022 the Author(s), licensee AIMS Press.